Toughening Of Epoxy Resin With Modified Liquid Natural Rubbers And Acrylonitrile-Butadiene Liquid Rubbers - Saleh, Abdulali Bashir Ahmed (2005)
The preparation of liquid natural rubber (LNR) by depolymerizing deprotenized natural rubber latex was carried out.